Construction of two-dimensional supramolecular nanostructure with aggregation-induced emission effect via host–guest interactions. (31st May 2019) - Liu, Hui; Pan, Qingyan; Wu, Chenyu; Sun, Jing; Zhuang, Tao; Liang, Tongling; Mu, Xueluer; Zhou, Xianfeng; Li, Zhibo; Zhao, Yingjie
Abstract : Formation of fluorescent two-dimensional supramolecular structure based on tetraphenylethene (TPE) derivative and CB[8]. Abstract : A tetraphenylethene (TPE) based water-soluble molecule was synthesized. The two-dimensional supramolecular nanostructure with an evident aggregation-induced emission effect was constructed through the host–guest interactions between the TPE derivative and CB[8]. The assembly process and the 2D structure were confirmed by 1 H-NMR spectroscopy, SEM, TEM and SAXS. A high affinity for DNA and significant fluorescence enhancement were observed for the TPE derivative, making it an excellent biological fluorophore stain for the intracellular DNA imaging of live cells.